Evaluation of Right Ventricular Systolic Function in Chagas Disease Using Cardiac Magnetic Resonance Imaging. (March 2017) - Moreira, Henrique T.; Volpe, Gustavo J.; Marin-Neto, José A.; Ambale-Venkatesh, Bharath; Nwabuo, Chike C.; Trad, Henrique S.; Romano, Minna M.D.; Pazin-Filho, Antonio; Maciel, Benedito C.; Lima, João A.C.; Schmidt, André
Abstract : Background—: Right ventricular (RV) impairment is postulated to be responsible for prominent systemic congestion in Chagas disease. However, occurrence of primary RV dysfunction in Chagas disease remains controversial. We aimed to study RV systolic function in patients with Chagas disease using cardiac magnetic resonance. Methods and Results—: This cross-sectional study included 158 individuals with chronic Chagas disease who underwent cardiac magnetic resonance. RV systolic dysfunction was defined as reduced RV ejection fraction based on predefined cutoffs accounting for age and sex. Multivariable logistic regression was used to verify the relationship of RV systolic dysfunction with age, sex, functional class, use of medications for heart failure, atrial fibrillation, and left ventricular systolic dysfunction. Mean age was 54±13 years, 51.2% men. RV systolic dysfunction was identified in 58 (37%) individuals. Although usually associated with reduced left ventricular ejection fraction, isolated RV systolic dysfunction was found in 7 (4.4%) patients, 2 of them in early stages of Chagas disease. Presence of RV dysfunction was not significantly different in patients with indeterminate/digestive form of Chagas disease (35.7%) compared with those with Chagas cardiomyopathy (36.8%) ( P =1.000). Conclusions—: In chronic Chagas disease, RV systolic dysfunction is more commonly associated with left ventricular systolic dysfunction, although isolated and early RV dysfunction can also be identified. Abstract : Supplemental Digital Content is available in the text.